Heart failure with preserved ejection fraction: Calculating the risk of future heart failure events and death - Schrutka, Lore; Seirer, Benjamin; Rettl, René; Dachs, Theresa-Marie; Binder, Christina; Duca, Franz; Dalos, Daniel; Badr-Eslam, Roza; Kastner, Johannes; Hengstenberg, Christian; Frommlet, Florian; Bonderman, Diana (Frontiers in Cardiovascular Medicine, 2022)
Objective We sought to develop a clinical model to identify heart failure patients with preserved ejection fraction (HFpEF) at highest risk for acute HF events or death. Methods and results Between 2010 and 2019, 422 patients with HFpEF were followed. Acute HF events occurred in 190 patients (45%), including 110 (58%) with recurrent hospitalizations. Those with recurrent events had worse 6-min walk test (p < 0.001), higher brain N-terminal prohormone natriuretic peptide (NT-proBNP, p < 0.001), and higher New York Heart Association functional class (NYHA, p < 0.001). Overall survival rates in patients with 1 HF event vs > 1 HF events were: at 1-year 91.6 vs. 91.8%, at 3-years 84.7 vs. 68.3% and at 5-years 67.4 vs. 42.7%, respectively (p < 0.04). The Hfpef survivAL hOspitalization (HALO) score revealed best predictive capability for all-cause mortality combining the variables age (p = 0.08), BMI (p = 0.124), NYHA class (p = 0.004), need for diuretic therapy (p = 0.06), left atrial volume index (p = 0.048), systolic pulmonary artery pressure (p = 0.013), NT-proBNP (p = 0.076), and number of prior hospitalizations (p = 0.006). HALO score predicted future HF hospitalizations in an ordinal logistic regression model (OR 3.24, 95% CI: 2.45–4.37, p < 0.001). The score performance was externally validated in 75 HFpEF patients, confirming a strong survival prediction (HR 2.13, 95% CI: 1.30–3.47, p = 0.002). Conclusions We developed a model to identify HFpEF patients at increased risk of death and HF hospitalization. NYHA class and recurrent HF hospitalizations were the strongest drivers of outcome.